THE ROLE OF CRM SYSTEMS IN ENHANCING CUSTOMER LOYALTY IN SMALL BUSINESSES (International Congress on Economics, Management and Business Studies, 2026)
This thesis examines the impact of Customer Relationship Management (CRM) systems on customer loyalty in small businesses. The study highlights how CRM tools help companies manage customer interactions, improve service quality, and increase customer retention. The findings suggest that the implementation of CRM systems contributes significantly to building long-term relationships with customers and enhancing business performance.
Keywords: CRM systems, small business, customer loyalty, digital technologies, customer retention, marketing.